Perencanaan Strategi Pemasaran Untuk Meningkatkan Penjualan Produk Batik Khas Jombang di Era New Normal - Listiani Hidayah; Nur Muflihah; Andhika Mayasari; Fatma Ayu Nuning Farida Afiatna (Universitas Batanghari Jambi, 2022)
UKM Batik Tulis New Colet Jombang produces three types of batik, namely hand-written batik, stamped batik, and semi-written batik. The problem occurs when batik sales decline due to the Covid-19, so it requires planning a marketing strategy to increase sales in the new normal era. The study aims to determine the internal and exsternal factor in UKM Batik Tulis New Colet Jombang, planning a marketing strategy using SWOT, BCG, and QSPM methods. Internal factors consist of strengths and weaknesses, while external factors consist of opportunities and threats. The results of the SWOT matrix can be seen that difference between internal factors is 1,95 and eksternal factors is -0,19. This shows that position of SMEs in quadrant IV and requires a W-T (Weaknesses-Threats) strategy. The BCG matrix in the dogs position, meaning that sales level is low at 3,25% and has a market share of 0,97 times of the competitor. Furthermore, alternative strategy QSPM method that gets highest TAS score of 4,4 is alternative 1, which means that the SMEs must innovate products with creative motivies.